Recontextualization of the Law on Marriage Postponement Due to Family Bereavement in Javanese Tradition from the Perspective of Maqāṣid al-Sharī‘ah - Arifin, Hamdan; Mukhlishin, Ahmad; Alfi Khotamin, Nur (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This study examines the practice of marriage postponement due to the death of a family member within the Javanese community tradition in Sukajadi Village, as well as its legal recontextualization from the perspective of Maqāṣid al-Sharī‘ah. The research employs a qualitative approach using a field-based case study method through observation and in-depth interviews with traditional leaders, religious leaders, and families who have experienced marriage postponement. The findings reveal that the practice of marriage postponement constitutes a complex socio-religious phenomenon, influenced not only by emotional factors, but also by customary values, the collectivist structure of the family, and cosmological beliefs such as the momentum of Satu Suro. This postponement functions as a social mechanism to maintain harmony, emotional stability, and community cohesion, while also serving as a form of respect for bereaved families. From the perspective of Maqāṣid al-Sharī‘ah, this practice can be understood as an effort to preserve maslahah through the protection of lineage (ḥifẓ al-nasl) and intellect (ḥifẓ al-‘aql), by ensuring psychological and social readiness in establishing a family. Furthermore, this tradition reflects the application of the concept of ‘urf ṣaḥīḥ as well as legal maxims that emphasize the prevention of harm and adaptation to changing circumstances. This study concludes that the tradition of marriage postponement is not static, but rather undergoes transformation through negotiation between custom, religion, and modern rationality, thereby remaining relevant within the framework of Islamic law oriented toward maslahah.